2017
DOI: 10.1371/journal.pone.0186250
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility of different mouse strains to oxaliplatin peripheral neurotoxicity: Phenotypic and genotypic insights

Abstract: Peripheral neurotoxicity is one of the most distressing side effects of oxaliplatin therapy for cancer. Indeed, most patients that received oxaliplatin experience acute and/or chronic severe sensory peripheral neuropathy. However, despite similar co-morbidities, cancer stage, demographics and treatment schedule, patients develop oxaliplatin-induced peripheral neurotoxicity with remarkably different severity. This suggests individual genetic variability, which might be used to glean the mechanistic insights int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
67
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 57 publications
(70 citation statements)
references
References 40 publications
(48 reference statements)
0
67
2
Order By: Relevance
“…No significant differences were found between LT and HT animals regarding anxiety-like behavior (F [1,46] = 2190, n.s.). As previously shown, 5 in the D/L paradigm, we observed that SNI-L animals presented an increased anxiety-like behavior when compared with SNI-R animals (F [1,43] = 4.108, P < 0.05).…”
Section: Anxiety-like Behaviormentioning
confidence: 77%
See 4 more Smart Citations
“…No significant differences were found between LT and HT animals regarding anxiety-like behavior (F [1,46] = 2190, n.s.). As previously shown, 5 in the D/L paradigm, we observed that SNI-L animals presented an increased anxiety-like behavior when compared with SNI-R animals (F [1,43] = 4.108, P < 0.05).…”
Section: Anxiety-like Behaviormentioning
confidence: 77%
“…Independent of threshold, these parameters were statistically correlated (Pearson correlation = −0,480; P < 0.01; Figure 2C). SNI LT and SNI HT show no differences regarding lesion side comparison (F [1,46] = 0.002, n.s.). Later assessment, after the application of the battery of behavioral tests and the day before sacrifice, a similar pattern was observed for evoked (F [4,55] = 368.006, P < 0.001), spontaneous pain-like behaviors (F [4,55] = 3760, P < 0.01; Sham vs SNI LT …”
Section: Pain Measurementsmentioning
confidence: 85%
See 3 more Smart Citations